Discretionary measures of active labor market policy: the German employment promotion reform in perspective - Fertig, Michael; Schmidt, Christoph M. (Discussion paper series, 2000)
This paper provides a preliminary assessment of recent reforms of German employment promotion policy. While several recent studies analyze the impact of measures of employment promotion for the case of Germany, no comparable study exists on the aggregate level, thus precluding any assessment of the overall impact of such measures. The reform of 1998 recognized for the first time in the history of German employment promotion that evaluation should be an integral part of the delivery of policy interventions. Yet, while this has led to an important first step - the systematic collection of data - evaluation itself has mistakenly been understood by the legislator as a pure accounting exercise. We discuss this problem from the perspective of the recent evaluation literature in economics and statistics, thus providing a frame of reference for performing credible scientific evaluation of employment promotion policy.